Phonological neighbourhood density: effects in a rhyme awareness task in five-year-old children - DE CARA, BRUNO; GOSWAMI, USHA (Journal of child language, 2003)
Phonological awareness skills are critical for reading acquisition, yet relatively little is known about the origins of phonological awareness. This study investigates one plausible source of the emergence of phonological awareness, phonological neighbourhood density. As vocabulary grows, the number of similar-sounding words in the child's mental lexicon increases. This could create developmental pressure to develop awareness of sub-units within words such as syllables, rhymes and phonemes. If this is the case, then neighbourhood density effects should be discernible in phonological awareness tasks. Children should be more successful in these tasks with words from dense phonological neighbourhoods, as they should show greater awareness of sub-units within these words. We investigated this hypothesis in a group of 48 five-year-old children, most of whom were pre-readers. The five-year-olds with a high vocabulary age showed neighbourhood density effects in a rhyme oddity task, but five-year-olds with lower vocabulary ages did not. This suggests that vocabulary acquisition and consequent neighbourhood density effects are indeed one source of the emergence of phonological awareness skills in pre-readers.